PPDPF promotes the progression of esophageal squamous cell carcinoma via c-Myc/CD24 axis - Ning Ma; Wei Chen; Yu Chen; Xiang Wang; Bing Zhu; Kai Ding; Lin Qiu; Jing-jing Li; Jing-Yi Huang; Xin Liang; Yan-Jun Xiang; Qian-Zhi Ni; et al. (Journal for ImmunoTherapy of Cancer)
Background Despite a series of attempts during the last decades, the prognosis for esophageal squamous cell carcinoma (ESCC) remains poor. Although clinical immunotherapy trials have shown encouraging results, their benefits are limited. This study aims to identify novel targets for immunotherapy in ESCC.Experimental design ESCC cell lines and mouse models were used to identify the tumor-promoting function of pancreatic progenitor cell differentiation and proliferation factor (PPDPF) and evaluate the effect of blockade of CD24. RNA sequencing was performed to profile transcriptomic changes upon PPDPF deficiency. Fluorescence microscopy-based phagocytosis assay and flow cytometry were employed to analyze macrophage phagocytosis. Immunoblotting, glutathione S-transferase-pulldown assay and co-immunoprecipitation assay were conducted to investigate the mechanism underlying the tumor-promoting role of PPDPF in ESCC. Clinical samples were analyzed to further validate the findings from preclinical models.Results The expression of PPDPF was significantly upregulated in ESCC. Deficiency of PPDPF inhibited the development of ESCC in mice. Mechanistically, PPDPF interfered with the c-Myc-GSK3β interaction and enhanced the protein stability of c-Myc, which increased the expression of CD24 and therefore promoted immune escape from macrophage phagocytosis. Positive correlations between PPDPF, c-Myc, and CD24 were observed in clinical samples. Anti-CD24 monotherapy effectively inhibited the ESCC tumor growth in mice.Conclusions PPDPF acts as an oncoprotein in ESCC by positively regulating the c-Myc/CD24 axis. These findings provide a potential effective target for immunotherapy in ESCC.